Thermal analysis of coordination compounds. Part 3. Thermal decomposition of platinum complexes containing triphenylphosphine, triphenylarsine and triphenylstibine - Barbieri, Roberto Santos; Bellato, C. R. [UNESP]; Massabni, A. C. [UNESP] (Elsevier B.V., 1995)
Studies by thermogravimetric analysis (TG) and differential thermal analysis (DTA) of the complexes [PtCl2L2] (L is PPh3, AsPh3, SbPh3), [PtLn] (n = 3, L is SbPh3; n = 4, L is PPh3, AsPh3); [(PtL3)2N2]; [(PtL3)2C2] and [Pt(CO)2L2] (L is SbPh3) are described. Analysis of the TG and DTA curves showed that Pt(II) complexes of the type [PtCl2L2] have a higher thermal stability than the corresponding Pt(0) complexes of the type [PtLn], with the exception of [Pt(SbPh3)3], which is more stable than [PtCl2(SbPh3)2]. Thermal stabilities of each of the complexes are compared with those of the others in the series. Mechanisms of thermal decomposition of complexes of the types [PtCl2L2] and [PtLn] are proposed. Residues of the samples were characterized by chemical tests and IR spectroscopy. The residue from the thermal decomposition of [PtCl2L2] (L is PPh3, AsPh3) and [Pt(PPh3)4] is metallic platinum. For [Pt(AsPh3)4] the residue is a mixture of Pt and As, whereas for the complexes containing SbPh3 the residues are mixtures of Pt and Sb. In these cases, the proportional contents of Pt and As or Pt and Sb correspond to the stoichiometry of these elements in the respective complexes. The complexes {[Pt(SbPh3)3]2N2}, {[Pt(SbPh3)3]2C2} lose N2 or the ethynediyl group at 130-150°C and are transformed into [Pt(SbPh3)3]. © 1995.
Keywords: Platinum complexes; Thermal analysis; Thermal decomposition; Triphenylarsine; Triphenylphosphine; Triphenylstibine